PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP KEPUASAN NASABAH PENGGUNA BNI MOBILE BANKING MELALUI CITRA BANK SEBAGAI VARIABEL INTERVENING - Sri Nawangasari; Nadea Dwirahma Putri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
This study aims to determine the effect of e-service quality and e-trust on customer satisfaction of BNI Mobile banking users through the image of the bank as an intervening variable. Data used in this study are primary data, data collection through questionnaires with a total sample of 185 respondents who are